2004
DOI: 10.13031/2013.15689
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Yield and Grade Response to Nitrogen Applied Daily Through a Subsurface Drip Irrigation System

Abstract: Nitrogen is typically applied to cotton (Gossypium hirsutum L.) in two or three split applications, however, with subsurface drip irrigation (SDI), nitrogen can be applied daily. The major objective was to show yield and grade response of cotton where nitrogen was applied daily through a SDI system at two nitrogen application strategies compared with overhead sprinkler (SP) and non-irrigated (DRY) regimens. The SDI system provided daily irrigation and nitrogen to a randomized block design with three irrigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…Hence, SDI can reduce percolation below the root zone (Hanson and May 2004) and decrease groundwater NO 3 --N pollution (Phene 1999). Meanwhile, too much N fertilizer application does not increase crop production (Camp et al 1997;Thompson et al 2002a, b;Sorensen et al 2004;Mahajan and Singh 2006;Cabello et al 2009). SDI has higher soil fertility after potato harvesting compared with DI, although this effect is not significant (Selim et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, SDI can reduce percolation below the root zone (Hanson and May 2004) and decrease groundwater NO 3 --N pollution (Phene 1999). Meanwhile, too much N fertilizer application does not increase crop production (Camp et al 1997;Thompson et al 2002a, b;Sorensen et al 2004;Mahajan and Singh 2006;Cabello et al 2009). SDI has higher soil fertility after potato harvesting compared with DI, although this effect is not significant (Selim et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, water deficit has been reported in several studies to cause various physiological disorders in cotton plants and ultimately to reduce cotton yield (11,12,19,21,22,29,32,34,36). In contrast, several studies have shown that irrigation increased seed cotton yield compared to dryland cotton yield (3,7,8,9,25,35,38). On the other hand, the absence of response to irrigation in some cotton studies was attributed to inadequate irrigation, restricted root growth, or insufficient rainfall (4,9,10,13).…”
Section: Introductionmentioning
confidence: 99%
“…Subsurface drip systems are adaptable to variations of field shape making them an important consideration in the Southeast. In recent years, drip irrigation has been expanded with good success on field crops such as corn (Zea mays L.) (Lamm et al, 1997(Lamm et al, , 2001Mitchell, 1981;Mitchell and Sparks, 1982;Powell and Wright, 1993), cotton (Gossypium hirsutum L.) (Camp et al 1997;Sorensen et al, 2004), and peanut (Jordan et al, 2002;Sorensen et al, 2001a, b;Zhu et al, 2004). Irrigation SDI laterals have been installed at 0.2 and 0.3 m soil depths (Bucks et al, 1981;Camp et al, 1989;Phene et al, 1987;Tollefson, 1985) on cotton, corn, fruits, and vegetables.…”
mentioning
confidence: 99%